2013
DOI: 10.1177/183693911303800203
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Early Childhood Education and Care Services in Australia

Abstract: THIS PAPER REPORTS CONCLUSIONS about the quality of early childhood education and care (ECEC) services from E4Kids, a large-scale longitudinal study of three types of ECEC services in two Australian states. A little more than 250 preschool classrooms had complete data in 2010; two measures of ECEC quality were applied-the CLASS and selected subscales of the ECERS-R. Overall, Australian ECEC averaged in the medium range on most measured components of quality, with the exception of personal care routines and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 15 publications
5
39
0
Order By: Relevance
“…In this CLASS Pre-K study of the outdoor environment, the emotional support domain achieved the highest scores, and the instructional support domain achieved the lowest scores, a finding that is consistent with other CLASS Pre-K studies of indoor learning environments (Curby et al 2010;LaParo et al 2004;Sandilos and DiPerna 2011;Tayler et al 2013). This outcome may be a reflection of an ECEC environment where children's social and emotional wellbeing is paramount and valued as being more crucial for learning and development than academic achievement.…”
Section: Class Pre-k In Outdoor Early Childhood Education and Care Cesupporting
confidence: 90%
See 2 more Smart Citations
“…In this CLASS Pre-K study of the outdoor environment, the emotional support domain achieved the highest scores, and the instructional support domain achieved the lowest scores, a finding that is consistent with other CLASS Pre-K studies of indoor learning environments (Curby et al 2010;LaParo et al 2004;Sandilos and DiPerna 2011;Tayler et al 2013). This outcome may be a reflection of an ECEC environment where children's social and emotional wellbeing is paramount and valued as being more crucial for learning and development than academic achievement.…”
Section: Class Pre-k In Outdoor Early Childhood Education and Care Cesupporting
confidence: 90%
“…The overall scores from CLASS Pre-K in this study indicate that the emotional support and classroom organization domains are in a high range of interaction quality, and that the instructional support domain is in the medium range. These ranges are higher than in other studies using CLASS Pre-K. For example, in other studies the mean scores for the emotional support and classroom organization domains were in the medium range, and the mean Instructional Support scores were in the low-medium range (Tayler et al 2013;Sandilos and DiPerna 2011). Conversely, a study in Finland using CLASS (Pakarinen et al 2010) found similar patterns to the current study with higher ranges reported.…”
Section: Class Pre-k In Outdoor Early Childhood Education and Care Cementioning
confidence: 63%
See 1 more Smart Citation
“…ECEC quality is a multidimensional concept and broadly defined aims at promoting children's well-being and positive developmental outcomes (Layzer and Goodson, 2006 [1] ). A common distinction is made between structural characteristics, process quality and staff's beliefs (Howes et al, 2008 [2] ; NICHD Early Child Care Research Network, 2002 [3] ; Pianta et al, 2005 [4] ; Sylva et al, 2006 [5] ; Thomason and La Paro, 2009 [6] ). Structural quality entails the distal and regulable factors, such as child-staff ratios, group size and staff training/education (Abbott-Shim, Lambert and McCarty, 2000 [7] ; Burchinal et al, 2010 [8] ; Barros et al, 2016 [9] ; Howes et al, 2008 [2] ; NICHD Early Child Care Research Network, 2000 [10] ; Thomason and La Paro, 2009 [6] ).…”
Section: Introductionmentioning
confidence: 99%
“…ECEC services across Australia are diverse, with educators from varied educational backgrounds, with a range of qualifications, professional learning, and experiences. Early learning programs contrast in terms of their overall quality [84] and educators work with children and families with unique strengths and challenges [85,86]. The comprehensive nature of the needs assessment in Step 1 assisted the intervention design group to define program goals.…”
Section: Discussionmentioning
confidence: 99%